Hubungan Aspek Spiritual: Transpersonal Dengan Kepatuhan Berobat Pada Lansia Dm Di Desa Pacing Sukosewu Bojonegoro - Zainal Abidin, Ahmad; Arif Agustiar (Journal of Pubnursing Sciences, 2024)
Background: Diabetes Mellitus is part of a form of degenerative disease which is still a special concern for the world of health, because it has its own frightening threat in society, so that adequate compliance is needed in terms of its spirituality. The purpose of this study was to analyze the relationship between spiritual: transpersonal aspects and adherence to treatment in the elderly DM in Pacing Sukosewu Village, Bojonegoro. Method: The research method used a non-experimental cross sectional approach with a sample size of 59 using a simple random sampling technique taking into account the inclusion criteria, namely elderly people with a permanent domicile, able to read and write and willing to be respondents, carried out in November-December 2023 and using Spearman's statistical tests. rho with a confidence level of 95% (ᾳ=0.05). Results: The results of this study obtained a p value using Spearman's rho correlation analysis of 0.000, which is less than α 0.05, which means that there is a significant relationship between spiritual: transpersonal aspects and adherence to diabetes mellitus treatment. The closeness value of the relationship in this study was 0.587, which means that the closeness is in the strong category. Conclusions: The conclusion of this research is that there is a significant relationship between the spiritual aspect: transpersonal and adherence to treatment in the DM elderly in Pacing Sukosewu Village, Bojonegoro, so it is very important for every DM sufferer to always pay attention to the management of the therapy they are undergoing for the quality of their health.